Detection and analysis of holes and bumps on road surfaces [Yol yüzey bozuklarinin tespit ve analizi] - (:unkn) unknown (IEEE Computer Society, 2014)
In this study, the road surface irregularities (pits, bumps, holes, speed breakers, etc.) is intended to be detected and identified with a system to be placed on the vehicles. For this purpose; a vibration-sensitive system is designed consisting of sensors, processor, and GPS receiver as hardware and the algorithms to be used for analyzing the obtained data. With the use of 3-dimensional acceleration sensors in the system, the measurements at the vehicles (vehicle speed/acceleration, the severity of the concussion and location information) are transferred to a database and then the resulting data are analyzed. Exact locations of pits and bumps are determined and their magnitudes are estimated. © 2014 IEEE.
Keywords: 3-dimensional acceleration sensors; hole and bump detection; road surface irregularities